Structure-Functional Activity Relationship of β-Glucans From the Perspective of Immunomodulation: A Mini-Review - Han, Biao; Baruah, Kartik; Cox, Eric; Vanrompay, Daisy; Bossier, Peter (Frontiers in Immunology, 2020)
β-Glucans are a heterogeneous group of glucose polymers with a common structure comprising a main chain of β-(1,3) and/or β-(1,4)-glucopyranosyl units, along with side chains varying branching and lengths. β-Glucans initiate immune responses via immune cells, which become activated by binding of the polymer to specific receptors. However, β-glucans from different sources are different in their structure, conformation, physical properties, binding affinity to receptors, and thus biological functions. The mechanisms behind this are not fully understood. This mini-review provides a comprehensive and up-to-date commentary on the relationship between β-glucans’ structure and function in relation to their use for immunomodulation.